The new victorians a young woman's challenge to the old feminist order - Denfeld, Rene (Warner Books, 1995)
Why do so many young women who believe strongly in equal rights refuse to call themselves feminists? Does feminism's counterproductive obsession with date rape, pornography, and goddess religions alienate young women - and lead the movement toward a dangerous alliance with the religious right? Is the agenda of today's women's movement uncomfortably similar to a Victorian crusade for repression? Rene Denfeld, a young woman born a year after the foundation of the National Organization for Women, says feminist leaders are out of touch. In the movement's latest obsessions, Denfeld finds a complete reversal of the movement's progress made since the 1970s. This decade's hypersensitive feminist - fearful, disillusioned, and adamantly anti-male - bears a strong resemblance to the dainty, sheltered, chaste Victorian lady of a century ago. And this is why, Denfeld says, young women are abandoning the feminist movement. Rene Denfeld cuts to the roots of the Anti-Phallic campaign, male bashing, and sexual politics; victim Mythology. Why date rape has become an excuse to blame men, and excuses women from responsibility regarding their sexual choices; the Anti-Pornography Crusade. How anti-pornography activists teach that sex is something decent feminists should not discuss; and goddess worship, or why new feminist visions of religion are a throwback to the Victorian view that women are by nature morally superior to men - and how this keeps women weak. Offering realistic alternatives to ideologically rigid and sometimes ridiculous doctrine, The New Victorians is a rallying cry for young women to take back feminism - and be proud of it.